Evaluation of Changes in Preoperative Cortical Excitability by Navigated Transcranial Magnetic Stimulation in Patients With Brain Tumor - Neville, Iuri Santana; Gomes dos Santos, Alexandra; Almeida, Cesar Cimonari; Hayashi, Cintya Yukie; Solla, Davi Jorge Fontoura; Galhardoni, Ricardo; de Andrade, Daniel Ciampi; Brunoni, Andre Russowsky; Teixeira, Manoel Jacobsen; Paiva, Wellingson Silva (Frontiers in Neurology, 2021)
Background: This prospective study aimed to evaluate the cortical excitability (CE) of patients with brain tumors surrounding or directly involving the corticospinal tract (CST) using navigated transcranial magnetic stimulation (nTMS). Methods: We recruited 40 patients with a single brain tumor surrounding or directly involving the CST as well as 82 age- and sex-matched healthy controls. The patients underwent standard nTMS and CE evaluations. Single and paired pulses were applied to the primary motor area (M1) of both affected and unaffected cerebral hemispheres one week before surgery. The CE parameters included resting motor threshold (RMT), motor evoked potential (MEP) ratio for 140% and 120% stimulus (MEP 140/120 ratio), short interval intracortical inhibition (SICI), and intracortical facilitation (ICF). Motor outcome was evaluated on hospital discharge, on 30-day and 90-day postoperative follow-up. Results: In the affected hemispheres of patients, SICI and ICF were significantly higher than in the unaffected hemispheres (p= 0.002 and p= 0.009, respectively). The 140/120 MEP ratio of patients unaffected hemispheres was lower than in controls (p = 0.001). Patients with glioblastomas (GBM) had a higher interhemispheric RMT ratio than patients with grade II and III gliomas (p = 0.018). It was observed a weak correlation among the RMT ratio and the preoperative motor score (R2 = 0.118, p = 0.017), and the 90-day follow-up (R2 = 0.227, p = 0.016). Conclusion: Using preoperative nTMS, we found that brain hemispheres affected by tumors had abnormal CE and that patients with GBM had a distinct pattern of CE. These findings suggest that tumor biological behavior might play a role in CE changes.